Androcentrismo acima de tudo - Masculino genérico acima de todas (e de todes) - O patriarcado linguístico nos manuais de redação tocantinenses - Souza, Paulo Anizio Martins de (2024)
The irrevocable gender marks of Portuguese have as a consequence the use of the generic masculine. This can be bypassed, nonetheless, depending on the strategies proposed by manuals for gender inclusive writing, to prevent cis and trans women as well as individuals of other genders or non-binary from being hidden by language. An ideal linguistic representation, however, should embrace all social genders in the strategies proposed by writing manuals. On the other hand, language itself holds some aversion to some of those strategies, especially the ones suggested by neutral language such as the propositions of ending words with “@”, “x” or “e”. Consequently, LGBTQ-phobic groups, or those in favor of Brazil above all else stand up to defend under the banner of God, Nation and Family an allege defense of their mother language when, in fact, they seem to wish to prevent discussions of gender and sexuality to be held in different social circles, especially at school. Amidst this Bolsonaro-like moralist setting – despite the reelection of the President Lula to the Executive Power, or because of that reelection – that we aim at discussing how IFTO (2017), UFT (2021), MP-TO (2017) and TCE-TO (2013), manuals and guides for official communications used in the state of Tocantins, Brazil, are patriarchal, androcentric and sexist. Our general objective will be, then, to promote a description, accounting and discussion of how these manuals and official writing guides, including the Writing Manual of the Presidency of the Republic, lack, in what they prescribe and exemplify with their file models, the that is proposed by gender- inclusive language. In order to achieve this general objective, we will have the following specific objectives: to address the distinction between inclusive and gender-neutral language, with its manifestations in Brazil and in other countries, as well as how it is received politically, socially and linguistically; discuss gender marking in Brazilian Portuguese and the gynophobic, lgbtphobic and sexist consequences, in linguistic and cognitive terms, of this standardized marking; and, finally, draw attention to the unequal and exclusive way in which different genders and sexual orientations are treated by the manuals and official writing guides in question, which can be gleaned from the examples and models that we will extract from them, counting them and discussing their results. To contemplate the purposes of this dissertation will serve as our main references Almeida (2020), Bagno (2017, 2020) Barbosa Filho (2022), Bentes, Cruz e Mendes (2022), Bourdieu (2022 [1930]), Burigo (2016), Caldas-Coulthard (2007), Carvalho (2022), Cassiano (2022), Cavalcante (2022), Fischer (2020), Franco and Cervera (2006), Freitag (2022), Glozman (2022), IFAL (2018) , Kilomba (2019), López et al (2012), Mäder (2015), Mercosur/RAADH (2018), Moura and Mäder (2022), Oliveira (2022), Pessotto (2019), Rajagopalan (2000), Rio Grande do Sul (2014), Schwindt (2020) and Woolf (2014 [1923]). As for its object, method, approach, objectives and purpose, the work that we will present will be bibliographic, deductive, quantitative-qualitative, exploratory and basic.